Try NerdPal! Our new app on iOS and Android

# Solve the quadratic equation $y-\frac{3}{4}-\frac{y^2}{4}=0$

## Step-by-step Solution

Go!
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

### Videos

$y=3,\:y=1$
Got another answer? Verify it here!

## Step-by-step Solution

Problem to solve:

$y-\frac{3}{4}-\frac{y^2}{4}=0$

Specify the solving method

1

We need to isolate the dependent variable $y$, we can do that by subtracting $\frac{-y^2}{4}-\frac{3}{4}$ from both sides of the equation

$y=-\left(\frac{-y^2}{4}-\frac{3}{4}\right)$

Learn how to solve quadratic equations problems step by step online.

$y=-\left(\frac{-y^2}{4}-\frac{3}{4}\right)$

Learn how to solve quadratic equations problems step by step online. Solve the quadratic equation y-3/4-(y^2)/4=0. We need to isolate the dependent variable y, we can do that by subtracting \frac{-y^2}{4}-\frac{3}{4} from both sides of the equation. Simplify the product -(\frac{-y^2}{4}-\frac{3}{4}). Grouping terms. Combine all terms into a single fraction with 4 as common denominator.

$y=3,\:y=1$
SnapXam A2

### beta Got another answer? Verify it!

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

$y-\frac{3}{4}-\frac{y^2}{4}=0$